Estudios epidemiológicos de patógenos bacterianos transmitidos por garrapatas en áreas urbanas y periurbanas del Área Metropolitana de Buenos Aires - González, S. (2021)
Urbanization has created a new geography, where there are no longer metropolitan areas surrounded by well-defined rural areas. Urban, semi-urban and semi-rural areas create an urban-rural interface, and in turn converge with natural areas (in some cases areas protected) in an urban-wild interface. All these areas are interrelated, allowing a large circulation of people, domestic animals, food products, and traffic of fauna (legal and illegal), providing new opportunities for the dispersal of pathogens and vectors. The increase of human and animal cases of infections caused by tick-borne pathogens in urban and peri-urban areas in recent years, together with the appearance and / or presence of infectious agents originating in natural areas, is closely related with these interfaces. In this sense, most domestic and wild animals (especially synanthropic) present in urban and peri-urban environments can act as hosts for some species of ticks and, in turn, be exposed to a variety of pathogens to which they may be susceptible. To analyze the richness of tick species in the urban-natural interface, in the Autonomous City of Buenos Aires, with emphasis on protected urban areas and neighboring neighborhoods, studies were carried out in the Rodrigo Bueno neighborhood (with high epidemiological risk and in close relationship with the Costanera Sur Ecological Reserve) and in the Ciudad Universitaria - Costanera Norte Ecological Reserve, both in the environment and in companion animals. Studies are currently being carried out on ticks and associated pathogens in areas of urban-rural-natural interfaces in the Exaltación de la Cruz district (Province of Buenos Aires). These studies contribute to the knowledge about the epidemiology of microorganisms transmitted by ticks in urban and peri-urban environments, within the framework of the "One Health" concept.